Prevalence and chemotherapy of babesiosis among Lohi sheep in the Livestock Experiment Station, Qadirabad, Pakistan, and environs - Rashid,A (2010)
A total of 310 blood smears were collected from sheep of the Livestock Experiment Station, Qadirabad, Sahiwal district, Pakistan, and surrounding areas. The samples were examined microscopically and 30 (9.67%) were positive for babesiosis. The animals were divided into two groups (A and B) for chemotherapy. Group A sheep were treated with diminazene diaceturate while group B animals received imidocarb dipropionate. Drug efficacy was determined by negative blood smear examination. Diminazene diaceturate effectiveness against babesiosis was 80% while that of imidocarb dipropionate was 100%. Hematological studies revealed a significant decrease in hemoglobin concentrations and hematocrit values for Babesia-positive animals compared to healthy controls.